Caliometric characterisation of crop production byproducts - Jóvér, János; Antal, Károly; Éri, László (Acta Agraria Debreceniensis, 2014)
By the decreasing tendency of the fossil energy resources more emphasis put on the usage of renewable energy resources. The consideration of environmental protection and the efforts of the European Union make current the widespread usage of renewable energy within biomass energy. One of the determinative trends of biomass energy is the direct combustion of biomass. Characteristically woody stocks are produced for this aim, but there is a considerable potential in several byproducts of growing herbaceous plants or of other processes.In our study three byproducts of plant production have been investigated which appeared at the harvest. The Higher Heating Values of wheat, maize and sunflower byproducts have been determined by an IKA C2000 Basic adiabatic calorimeter. According to the statistical analysis of the measured data the HHV of the byproducts are different, and these values are in a negative correlation with the amount of ash in % (R2=0.873) appeared by the combustion.